How does the corporate life cycle influence Vietnamese firms corporate social responsibility? - Luu Bich Thu; Nguyen Vinh Khuong (Cogent Economics & Finance, 2023)
This study investigates the association between the corporate life cycle and corporate social responsibility (CSR) disclosure in Vietnam. We hypothesize that the ability and motivation of firms to engage in various CSR activities at each stage of the corporate life cycle are different. Data are collected from 218 companies listed on the HOSE and HNX exchanges in Vietnam from 2014 to 2018 to measure the CSR according to the 2016 GRI General Standards, Parts GRI 200, GRI 300, and GRI 400. Using 2SLS estimation, the empirical findings of our study are consistent with our hypothesis. Our findings suggest that the introduction and growth stages are positively associated with CSR disclosure. Firms in the decline and shake-out phases no longer focus much on CSR disclosure, which shows that older firms do not invest in CSR activities as much as young firms. This study has two contributions. First, the research findings help to expand the literature in the Vietnamese context by applying business life cycle theory and aligning CSR with corporate life cycle stages. Second, the results of this study contribute to managerial implications in making CSR dimension decisions.
Keywords: G12; G32; M14; M40; 330; Corporate social responsibility; Life cycle; Vietnam